Aligning academic learning with economic demands in French tertiary education: a mixed methods study - Cadet, Christine (2016)
Discourses surrounding the effects of neoliberal ideology on the transformation of education from a public good into a commercial product have been widely reported in the literature. But how do these discourses translate to the micro level for teachers and heads of departments? This paper presents a small-scale study using a mixed methods research approach to examine English language teaching (ELT) professionals’ perceptions of the outcomes of the commodification of education in the French tertiary sector. The outcomes indicate that two key phenomena are being shaped by neoliberal constructs: changes affecting professional practices and emerging tensions between teachers and managers. Evidence suggests that pressures are placed on ELT professionals to extend their roles and their practices to respond to the needs of students or ‘clients’ in both the state and private sectors. At the same time, teaching contracts are being reigned in due to labour reforms, causing tensions. The main conclusion drawn from this study is that a disconnect exists between France’s traditional values-based education system and the rapidly advancing economic role of education. France’s public education is clearly at a crossroads: market-oriented changes are occurring on some levels but are not uniform across the system. The data suggests that, while the demand for English language instruction will expand, ELT professionals are nevertheless fearful of further exigencies embedded in neoliberal philosophy.